Avaliação do perfil eletroforético das proteínas séricas em matrizes pesadas (gallus gallus domesticus) da linhagem avian farm - Hasegawa, M. Y.; Fonteque, J. H. [UNESP]; Kohayagawa, A. [UNESP]; Boretti, L. P. [UNESP] (FapUNIFESP (SciELO), 2002)
This work is aimed to determine the profile of electrophoretic serum protein in healthy adult broiler breeders (Gallus gallus domesticus) of the Avian farm strain. Fifteen breeders aging 63 weeks from Conchas, city located in the State of São Paulo, were assessed. The biuret method was used to obtain the total serum protein values and protein fractions separation through electrophoresis technique in agarose gel, and film reading through densitometry in 520nM. Seven fractions were obtained, whereas, β 1 - globulin and β 2 - globulin were not cited by the authors in the textbooks checked. The prealbumin fraction was identified only in six out of 15 samples analyzed. In five breeders, it was observed the division of g - globulin into two fractions named g - 1 and g - 2, according to the electrophoretic mobilities. The relation albumin/globulin (A/G) found in the experiment agrees with the other authors cited, demonstrating that it decreases as the age increases.
Serum protein electrophoresis evaluation in adult broiler breeders (gallus gallus domesticus) of the avian farm strain
Keywords: Broiler breeders; Electrophoresis; Hen; Protein